PENGARUH MODEL PEMBELAJARAN TEAMS GAME TOURNAMENT BERBASIS PERMAINAN RANKING 1 TERHADAP KEAKTIFAN SISWA - Tarigan, Kelvin Paskah Pratama; Dedy, Adrianus; Ramadhani, Erfan (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to examine the effect of the Teams Game Tournament (TGT) learning model based on the Ranking 1 game on student activeness in Pancasila Education classes conducted in small classroom settings. Limited classroom space and low student participation often hinder the achievement of learning objectives. This research employed a quantitative method with a One-Group Pretest–Posttest Design. The study subjects were fifth-grade students at SD Negeri 148 Palembang, who studied in a confined classroom with a limited number of students. The findings indicate that the TGT model integrated with the Ranking 1 game significantly increased student activeness, both individually and in groups. Moreover, this learning model successfully created an enjoyable and competitive classroom atmosphere that encouraged positive interaction among students. Therefore, the Teams Game Tournament model based on Ranking 1 can be considered an effective strategy for enhancing student engagement and participation in limited learning environments.